Pembinaan Karakter Anak Sekolah Dasar Melalui Pembelajaran Literasi Kewargaan di Era Digital - Tsabitah Rafifah; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The development of increasingly advanced technology has both positive and negative impacts. As the next generation of the nation, awareness is needed in increasing civic literacy in the digital era. This is in line with the purpose of this study, which is to foster the character of elementary school children through civic literacy learning with its approaches to learning. By strengthening the spirit of citizenship, we want to produce a generation of qualified and qualified young people and able to actively contribute to the development of the nation and state in this digital era. Therefore, in civic literacy, it is very important to comprehensively prepare citizens to face these challenges with a firm and deep understanding. Through comprehensive civic literacy learning helps improve citizenship in society. This is an important key in building a harmonious and good society.